The Implementation Of Al-Mawardi's Adab Education In Preventing Bullying At Mauidzul Amin Al-Islamy Islamic Boarding School Pamekasan - Masrufah; Ali Ridho; Ismail (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
Adab (ethical education) is a crucial aspect in shaping the character of students (santri) in Islamic boarding schools (pesantren), particularly in preventing negative behaviors such as bullying that can damage social relationships among students. This study aims to analyze the implementation of adab education at Islamic Boarding School Mauidzul Amin Al-Islamy and its relevance in preventing bullying behavior within the pesantren environment, with reference to the values of adab education in Al-Mawardi’s thought. This research employs a qualitative approach with a field research design. Data were collected through observation, interviews with caregivers, administrators, and students, as well as documentation of various mentoring activities in the pesantren. The results indicate that adab education in this Islamic Boarding School is implemented through classical Islamic text studies, guidance from caregivers, spiritual development through Sufism studies, supervision by male and female teachers (ustadz/ustadzah) in dormitories, and the enforcement of pesantren regulations with educational sanctions. This implementation contributes to fostering students’ moral awareness and creating more harmonious social relationships, thereby serving as a preventive effort against bullying behavior.